1996
DOI: 10.1159/000276786
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Endothelin-1-Like Activity in the Vestibule of Normal Guinea Pigs

Abstract: Endothelin (ET) has been revealed to be a local hormonal regulator of pressure, fluid, ions and neurotransmitters. In order to investigate the mechanism of homeostasis within the microenvironment of the inner ear, the present study has examined the distribution of ET in the vestibule of normal guinea pigs, by immunohistochemistry using mouse antihuman ET IgGl monoclonal antibody. ET-like activity was identified in the sensory epithelial cells, supporting cells, dark cells, transitional cells, vestibular membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…ET-1 activity was detected in the modiolus, spiral ligament, stria vascularis, spiral prominence, Reissner's membrane, supporting cells of the organ of Corti, and spiral ganglion cells [10]. In the vestibule of normal guinea pigs, ET-like activity was identified in the sensory epithelial cells, supporting cells, dark cells, transitional cells, vestibular membrane, semicircular wall cells and vestibular ganglion cells [11]. ET-1-like activity was identified in the epithelial cells and subepithelial connective tissue of the endolymphatic sac and duct of normal guinea pigs [12].…”
Section: Introductionmentioning
confidence: 97%
“…ET-1 activity was detected in the modiolus, spiral ligament, stria vascularis, spiral prominence, Reissner's membrane, supporting cells of the organ of Corti, and spiral ganglion cells [10]. In the vestibule of normal guinea pigs, ET-like activity was identified in the sensory epithelial cells, supporting cells, dark cells, transitional cells, vestibular membrane, semicircular wall cells and vestibular ganglion cells [11]. ET-1-like activity was identified in the epithelial cells and subepithelial connective tissue of the endolymphatic sac and duct of normal guinea pigs [12].…”
Section: Introductionmentioning
confidence: 97%
“…It is the most potent vasoconstrictor. Later studies showed that endothelin 1 is widely distributed in cardiovascular and noncardiovascular system [2,3], and also distributed in endolymphatic sac, vestibule and stria vascularis of inner ear [4][5][6]. All the data suggests that endothelin 1 is involved in a wide variety of biological activities including action to maintain the homeostasis of pressure, fluid and electrolyte balance of inner ear.…”
Section: Introductionmentioning
confidence: 99%
“…It has many biological functions and plays a significant role in vasoconstriction and the regulation of fluid volume and ion balance. Endothelin-1-like activity has been demonstrated in the inner ear; 2 , 3 however, the role of endothelin 1 in maintaining cochlear homeostasis is not clear.…”
Section: Introductionmentioning
confidence: 99%